Competition and Cooperation in Social and Political Sciences Proceedings of the Asia-Pacific Research in Social Sciences and Humanities, Depok, Indonesia, November 7-9, 2016 Topics in Social and Political Sciences - Achwan, Rochman; Rukminto Adi, Isbandi (Taylor & Francis, 2018)
The book contains essays on current issues in Social and Political Sciences, such as the issues of governance and social order; social development and community development; global challenges and inequality; civil society and social movement; IT-based community and social transformation; poverty alleviation and corporate social responsibility; and gender issues. Asia and the Pacific are the particular regions that the conference focuses on as they have become new centers of social and political development. Therefore, this book covers areas that have been traditionally known as the social and political areas such as communication studies, political studies, governance studies, criminology, sociology, social welfare, anthropology and international relations. The book will help shed light on what social and political scholars in Asia and the Pacific have done in terms of research and knowledge development, as well as the new frontiers of research that have been explored and opening up, which can connect the two regions with the rest of the globe.